Collaboration of simulations and experiments for development and uncertainty quantification of a reduced char combustion model. (August 2017) - Iavarone, Salvatore; Isaac, Benjamin; Smith, Sean; Smith, Philip J.; Contino, Francesco; Parente, Alessandro
Abstract: Computational fluid dynamics (CFD) plays a decisive role in the development of cost-effective oxy-coal combustion technologies to improve process efficiency and to decrease pollutant emissions. The implementation of detailed physical models describing coal devolatilization, char oxidation, gas-phase reactions and pollutant formation ensures accurate CFD simulations of coal combustion but is still challenging for large-scale combustors due to the significant computational efforts required, especially in the framework of Large Eddy Simulation (LES). The development of reduced physics model with quantified model-form uncertainty is needed to overcome the challenges of performing LES of industrial coal-fired boilers. Reduced models must reproduce the main features of the detailed models and the capability of bridging scales and being predictive. A tight coupling of simulation and experiments is necessary to ensure predictivity with uncertainty quantification for a reduced model. This work proposes a combined experimental/numerical methodology that uses global sensitivity analysis to rank fundamental input parameters of a reduced char oxidation and gasification model describing reactions between char carbon and O2, CO2 and H2 O reagents in both air and oxy-coal conditions. A careful evaluation of uncertainty in the data, in the model form and in the model parameters is performed. The reference dataset, consisting of the experiments carried out in a laminar entrained flow reactor operated by Sandia National Laboratories, has been exploited. The methodology is based on the use of so-called instrument models to include all the physical sub-models and the sources of uncertainty considered in the experiments and in the numerical simulations and affecting the main quantities of interest, e.g. reaction rates. The quantified uncertainty in the instrument models provides the range of uncertainty for the reduced char combustion model. Then, the reduced model with quantified uncertainty will be validated against the experimental data. The reduced model capability to address heterogeneous reaction at the particle surface, mass transport of species in particle boundary layer, pore diffusion and internal surface area changes will be assessed.